From Organics to Ceramics? - Wood, Nigel (Annali di Ca’ Foscari: Serie Orientale)
Skeuomorphism in Chinese ceramics is a widespread phenomenon with examples known from the early Shang dynasty (sixteenth c. BC) through to modern times, and with metal, lacquer, jade and glass vessels all serving as models for the ceramics they inspired. With Neolithic pottery in China, however, the presence of skeuomorphic design is more difficult to assess. Nonetheless many Neolithic ceramics from northern China seem to embody influences from materials as various as basketwork, birch bark, leather and horn. This suggests that extensive skeuomorphism may once have operated at a much earlier stage in China’s ceramic history than the Bronze Age – namely the Neolithic period.